Trade linkages and transmission of oil price fluctuations in a model incorporating monetary variables - Farhad Taghizadeh-Hesary; Ehsan Rasoulinezhad; Naoyuki Yoshino (Asian Development Bank Institute (ADBI), 2017)
This study is an attempt to ascertain how sharp oil price changes can affect oil-exporting and oil-importing economies. To this end, a simultaneous equation model (SEM) was applied through a weighted two-stage least squares estimation method to different countries (21 cases) with business relations over the period from Q1 2000 to Q4 2015. In the case of oil-exporting countries - consisting of Iran, the Russian Federation, United Arab Emirates, Indonesia, and Kazakhstan - the findings revealed that they totally benefit from oil price increases. In the case of oil-importing countries, the effects are more diverse. To derive a better interpretation, we divided them into four groups: European Union (EU) members (Germany, Italy, the Netherlands, and Poland); East Asian nations (Japan; the People's Republic of China; the Republic of Korea; Viet Nam; Taipei,China; Singapore; and Hong Kong, China); Commonwealth of Independent States (Ukraine and Belarus); and others (the United States, India, and Turkey). The results showed that all these countries importing oil face a negative supply shock, except Turkey which benefits directly from an oil price shock. Furthermore, the indirect effect coefficient received through trade for all these countries was positive.
Keywords: Q43; C30; E32; 330; crude oil price; trade linkage; direct and indirect effect of oil shocks